(NsMQTENIE PRAWEDNYH(B: [(NpO\MA(B] / s (N~ASTX (B3s - (NnAWOI(B, (NaLI[ERs ((NtA[KENT(B: s (NfAN(B, s, 1968)
(Nw TRETIJ TOM UZBEKSKOGO PO\TA(B, (NMYSLITELQ I GOSUDARSTWENNOGO DEQTELQ aLI[ERA nAWOI (B(1441 - 1501) (NWO[LA PERWAQ PO\MA (B"(NsMQTENIE PRAWEDNYH(B" (NW SOSTAWE ZNAMENITOJ (B"(NhAMSY(B".s
rus
Keywords: (NpO\MAs; (NsTIHOTWORENIQs